Unique Specific Jumping Test for Measuring Explosive Power in Young Basketball Players: Differences by Gender, Age, and Playing Positions - Asaf Shalom; Roni Gottlieb; Pedro E. Alcaraz; Julio Calleja-Gonzalez (MDPI AG, 2024)
When playing basketball, players are required to have high explosive power, which requires the ability to move in efficient, specific, and game-specific movement patterns that combine both horizontal and vertical abilities. Differences have been seen between young male and female basketball players in this measure. The aim of this study was to examine differences in players' unique movements by gender, age, and playing positions using a novel test for basketball players. This study included 232 young basketball players, male and female, from a range of Israeli leagues, who were divided into three categories: under-14, under-16, and under-18. Our findings showed that males presented better results than females in all age categories. Moreover, females in the under-18 category presented better results than those in the under-14 category, but not more than those in the under-16 category. Differences in playing positions were only examined between males and females in the under-18 category, where players begin to specialize in playing positions, and here, guards showed better results than forwards and centers. Our conclusions highlight the importance of including unique, sport-specific tests in talent identification and selection processes, as these tests can provide valuable information about a player's skill set and potential for success. The findings are presented in an achievement table of the expected physical fitness results by age and gender for the benefit of basketball coaches and strength and conditioning coaches when assessing their players.